(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objectives: To characterize clientele with elimination stoma and to analyze the degree of implementation of the Health Care Policy of Ostomized Person in Diamantina/MG. Method: Descriptive and cross-sectional study. The sample consisted of 107 people with elimination stoma registered in the period from October 2013 to August 2015. The study involved two stages in which the profile of the clientele was characterized and the entire structure of the Health Care Policy of Ostomized Person was analyzed according to validated questionnaires. Results: It was found that most of the participants were men, elderly, with a recent stoma, white colour, married, employed by a farmer and retired, schooling from 1 to 5 years and salary range of 1 to 2 minimum wages. The precursor disease of the stomas was colorectal cancer. The Health Care Policy of Ostomized Person in Diamantina can be characterized as level II, with satisfactory, but not full implantation. Conclusion: It is expected that these discoveries may support guidelines for multidisciplinary orientation and public policies.